2019
DOI: 10.12659/aot.917047
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Structured Physical Activity Program on Serum Adipokines and Markers of Inflammation and Volume Overload in Kidney Transplant Recipients

Abstract: Departmental sources Background: Kidney transplantation (KTx) reverses most abnormalities related to chronic kidney disease (CKD), but sedentary lifestyle persists in most kidney graft recipients. Physical inactivity has been associated with altered adipokine profile and inflammation in CKD. We postulated that increased physical activity achieved through an individually-tailored program can reverse these changes. Material/Methods: We included 25 clinically stable KTx recipients at least 12 months after transpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
2
1
Order By: Relevance
“…Thus, in our study we examined the impact of PR on body composition as an alternative measure of muscle mass but found no impact of the intervention on this parameter. Prior studies examining the impact of exercise on body composition in CKD patients demonstrate conflicting results with some showing improvement in lean leg mass and SMI and others showing no effect 57‐59 . In our study, we found that patients with baseline wasting experienced greater loss of muscle mass following the intervention.…”
Section: Discussioncontrasting
confidence: 55%
“…Thus, in our study we examined the impact of PR on body composition as an alternative measure of muscle mass but found no impact of the intervention on this parameter. Prior studies examining the impact of exercise on body composition in CKD patients demonstrate conflicting results with some showing improvement in lean leg mass and SMI and others showing no effect 57‐59 . In our study, we found that patients with baseline wasting experienced greater loss of muscle mass following the intervention.…”
Section: Discussioncontrasting
confidence: 55%
“…Regular exercise also has a beneficial effect on circulating markers of chronic inflammation in kidney transplant recipients (KTRs) 19 . However, a study in 26 KTRs reported that lymphocyte and monocyte population phenotypes did not change in response to 2 months of regular moderate or highintensity interval training 20 .…”
Section: [H1] Chronic Inflammationmentioning
confidence: 99%
“…17 To offset some of the deleterious effects of poor diet and lack of PA, participation in a healthy lifestyle program can be pursued by kidney transplant recipients. [18][19][20][21][22][23] In this survey, an overwhelming majority of participants would participate in an online healthy lifestyle program if it were available. When asked about the design features of the healthy lifestyle program, many wanted the program to be 6 to 12 months in length.…”
Section: Discussionmentioning
confidence: 99%